Detection of Porcine DNA Residue in Various of Collagen Supplements - Septiani, Triayu (Indonesia Journal of Halal, 2024)
Collagen is the main protein that makes the connective tissue structure of vertebrates and can be found in interstitial tissue in almost all parenchymal organs with a function as a stabilizer and maintains the shape of these organs. Collagen can be divided into three major categories based on the source, collagen from cows, pigs and marine animals. Collagen derived from cows is extracted from skin and bones, but type of collagen derived from cows is takes of concern because of BSE or mad cow problems and is also reported to cause allergies in about 3% of the population. The alternative is using collagen from pork and marine animals. However, the use of pork collagen or contamination of pork collagen is prohibited for Muslims. The aims of this study to detection the residue DNA in collagen supplements and to identified the origin of DNA residue from non-halal materials. The results obtained from whole samples have purity in the range 1.25-4, and one sample with high purity of DNA ratio is 1.91. The results testing of collagen sample using RT-PCR (qPCR) showed that the value of Cq FAM values in positive control were 30.34 and 31.89, only one sample was amplified with Cq value 12.27 that has high difference from Cq value of positive control. Cq value of VIC from whole samples ranging of 29.41-31.91 means the sample also contained vertebrates.